Comparison of the results of medical approach and surgical approach of septic arthritis in native joints: a single-center retrospective study - Qiyuan Lu; Xiaoqiang Yang; Mengmeng Chen; Zhiqiang Mao; Houfu Ling (BMC Musculoskeletal Disorders)
Abstract Background The consequences of septic arthritis of natural joints may be devastating. The purpose of this study was to evaluate the functional results of medical approach and surgical approach for septic arthritis of native joints, and to explore whether the number of drainage tubes after arthroscopic surgery will affect the knee function of patients. Methods A single-center retrospective study was conducted on patients diagnosed with septic arthritis from January 2018 to January 2023. According to the improvement of clinical symptoms and daily activity ability of the joints, functional results of patients were divided into Complete recovery, Basic recovery, Minor recovery and No recovery. The main results are the joint function after medical and surgical approaches. The secondary outcome was knee function with different number of drainage tubes after arthroscopic surgery. Multivariate logistic regression analysis was used to determine the risk factors related to joint function. In addition, the types of bacteria were analyzed to explore whether they were related to the initial surgical failure rate. Results Among the 77 patients with septic arthritis, 27 patients were treated with medical approach, and 50 patients were treated with surgical approach (knee arthroscopy + synovectomy). There was no significant difference in the results of joint function at discharge and 6 months after discharge. There was no significant difference in the number of drainage tubes after knee arthroscopy on the recovery of knee joint function. There were no risk factors independently associated with joint function outcomes in this study. In the cases of initial surgical failure, the treatment failure rate was 13.0% in the multidrug-sensitive bacteria group, 100% in the methicillin-resistant Staphylococcus aureus group, and 58.3% in the other multidrug-resistant bacteria group (P = 0.001). Conclusions The results of this study indicate that medical methods may be as effective as surgical methods for functional recovery in patients with septic arthritis. The number of drainage tubes after knee arthroscopy had no significant effect on the recovery of knee joint function. Maybe the type of bacteria (gram negative or more aggressive ones) can play a role in the choice of treatment strategy. Further prospective studies with better methodology are needed.